Perpustakaan Umum Di BAgan Siapi - Api Kabupaten Rokan Hilir Dengan Pendekatan Arsitektur Hijau - Rudi Irawan; Ratna Amanati; Pedia Aldy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
According to the vision and mission Rokan Hilir Regency which one of them is to prepare self to educational society life, so it need to design a public library which is economical in using the nature resource, minimize the negatif impact, also be able toimproving the human life quality. Library is a space, a part of a building or the building it self which is used to keep books and other derivative which are usually kept according to thecertain formation to be read, not to be sold. The nature phenomenon which is menacing this earth is a global warming. To reduce that impact so we choose the green architecture as the approach in designing the public library. One of them is about the thermal pleasure, by set the site and building mass which can give the thermal pleasure to the user of public library.Because, the thermal is a thermal condition which can be felt by human, not by object, animal, and architecture, but is conditioned by the environment and the objects around thearchitecture or the mind condition of somebody who can expressing his satisfaction to the thermal environment. This public library is presented with the green architecture conceptwhich be expected will be used in this present and the future, for the better continuity of life. The design method which be used in this public library is the six criterion of the Green Building Index (GBI). (1) Energy efficiency; (2) The environmental quality in the space; (4) Material and resource; (5) Water efficiency; (6) Innovation. From the theory and method which be used in this design reaching the conclusion that in the strive to set the site and the building mass as the strive to reach the pleasure, we apply the green architecture in this public library design. To reach the thermal pleasure to the public library user, we do the strive to set the site and mass of the building by applying six criterion of Green Building Index (GBI) from the green architecture.Key Word: Public Library, Green Architecture, Thermal Pleasure